Effects of nitric oxide on large‐conductance Ca2+‐activated K+ currents in human cardiac fibroblasts through PKA and PKG‐related pathways. (5th September 2017) - Bae, Hyemi; Lim, Inja
Summary: The human cardiac fibroblast (HCF) is the most abundant cell type in the myocardium, and HCFs play critical roles in maintaining normal cardiac function. However, unlike cardiomyocytes, the electrophysiology of HCFs is not well established. In the cardiovascular system, Ca 2+ ‐activated K + (KCa) channels have distinct physiological and pathological functions, and nitric oxide (NO) plays a key role. In this study, we investigated the potential effects of NO on KCa channels in HCFs. We recorded strong oscillating, well‐maintained outward K + currents without marked inactivation throughout the test pulse period and detected outward rectification in the I‐V curve; these are all characteristics that are typical of KCa currents. These currents were blocked with iberiotoxin (IBTX, a BKCa blocker) but not with TRAM‐34 (an IKCa blocker). The amplitudes of the currents were increased with SNAP (an NO donor), and these increases were inhibited with IBTX. The SNAP‐stimulating effect on the BKCa currents was blocked by pretreatment with KT5823 (a protein kinase G [PKG] inhibitor) or 1 H‐[1, ‐2, ‐4] oxadiazolo‐[4, ‐3‐a] quinoxalin‐1‐one (ODQ; a soluble guanylate cyclase inhibitor). Additionally, 8‐bromo‐cyclic guanosine 3', 5'‐monophosphate (8‐Br‐cGMP) stimulated the BKCa currents, and pretreatment with KT5720 (a protein kinase A [PKA] inhibitor) and SQ22536 (an adenylyl cyclase inhibitor) blocked the NO‐stimulating effect on the BKCa currents. Furthermore, 8‐bromo‐cyclic adenosine 3', 5'‐monophosphate (8‐Br‐cAMP) activated the BKCa currents. These data suggest that BKCa current is the main subtype of the KCa current in HCFs and that NO enhances these currents through the PKG and PKA pathways.